Cerebral blood flow network differences correlated with cognitive impairment in mild traumatic brain injury - Duan, Min; Liu, Yin; Li, Fengfang; Lu, Liyan; Chen, Yu-Chen (Frontiers in Neuroscience, 2022)
Purpose: To examine whether the cerebral blood flow (CBF) and CBF connectivity differences are sex-specific and whether these differences are correlated with cognitive impairment in mTBI. Methods: Resting-state perfusion magnetic resonance imaging was performed in 40 patients with acute mTBI and 40 healthy controls by using pseudocontinuous arterial spin labeling within 14 days following injury. The differences in normalized CBF were first compared and CBF connectivity of the brain regions with significant CBF differences were compared next. The association between the normalized CBF and CBF connectivity differences and cognitive function were further investigated. Results: Men patients had lower normalized CBF in the frontal gyrus, temporal gyrus and hippocampus and decreased negative CBF connectivity between brain regions including the hippocampus, temporal gyrus, postcentral gyrus and lenticular nucleus, putamen, compared with men controls. Women patients had lower normalized CBF in the frontal gyrus, however had higher normalized CBF in the temporal gyrus and hippocampus, compared with women controls. Additionally, women patients showed increased positive CBF connectivity between the seed region of interest (ROI) of the right inferior temporal gyrus and temporal gyrus and frontal gyrus, and had increased positive CBF connectivity between the seed ROI of the right hippocampus and the temporal gyrus. Furthermore, men patients had higher CBF in the right middle temporal gyrus and left precentral gyrus than women patients. Conclusion: This study provides evidence of sex differences in both decreased and increased CBF and CBF connectivity and association with cognitive outcome in the acute stage after mTBI.